Objektivitas Riwayat dalam Tafsir Jāmi’ al-Bayān: Ekplorasi Formasi Diskursif aṭ-Ṭabarī - Faizah, Thoriqotul (Sunan Kalijaga Islamic State University, 2024)
The debate surrounding the subjectivity in aṭ-Ṭabarī’s use of history in his work Jāmi' al-Bayān challenges the perception of its popularity as a widely-referenced tafsīr bi ar-riwāyah (interpretation based on narration). The assumption that aṭ-Ṭabari defended tradition in his Quranic interpretation process necessitates an exploration of the contextual factors shaping his discursive formation. This study aims to uncover the interconnections within this formation by employing qualitative methods supported by archaeological analysis. The findings indicate that the intense intellectual debates during the Abbasid caliphate’s knowledge advancements influenced aṭ-Ṭabari’s interpretive model. The rationalistic tendencies that began to permeate Quranic interpretation were countered by aṭ-Ṭabarī’s decision to rely exclusively on well-known narrations from the Companions and Tabi'in. This approach is reflected in the interpretation of various verses on a majority scale. The intensity of the debates during aṭ-Ṭabarī’s era not only impacted interpretive methods but also extended to legal rulings and theological beliefs, often using Quranic arguments. Aṭ-Ṭabarī's response to this dynamic involved an interpretive model that emphasized the preeminence (tarjīḥ) of specific traditions, revealing his subjective inclinations. Similarly, his approach to responding to fiqh and theological issues, which often involved syllogism and linguistic analysis, demonstrates a tendency to choose meanings while critiquing the interpretive products of various schools of thought, indicating an inconsistency with the school he ostensibly supported. This aspect reveals aṭ-Ṭabarī’s independence from the prevailing mainstream schools of his time.